La fiabilité prévisionnelle d’une pile à combustible de type PEMFC - Nedjem Eddine Benchouia; Belgacem MADI; Mounir BENADJA (International Conference on Maintenance and Industrial Safety CIMSI'2017, 2017)
The objective of this paper is to propose a new method for calculating predictive reliability by applying the State Space Method (MEE) to PEMFC fuel cell systems. Our work focuses on estimating the reliability of the PEMFC fuel cell itself applied to components subject to damage, conversion systems (boost, buck), and storage systems.